Konstruktivisme Teknologi Dalam Pembelajaran selama Implementasi Kurikulum Merdeka di SMA Negeri 13 Surabaya - Kumairo, Mala Nur; Hidayah, Putri Fitria; Nisa, Vadilatun (Lembaga Yasin AlSys, 2023)
Education has the responsibility to integrate new values in students caused by advances in technology and science. Appropriate learning methods are needed because the education system evolves with the changing times. One branch of the philosophy of knowledge known as constructivism emphasizes the idea that the knowledge we have is the result of our own construction. The issue addressed in this research is how SMAN 13 Surabaya implements technological developments in its teaching. The aim of this research is to analyze the extent of active student participation in the learning process, particularly through the constructivist approach, and how technology can be optimized to facilitate learning activities. The research method used in this study is descriptive qualitative. The results indicate that the utilization of technology in learning at SMAN 13 Surabaya is not yet running optimally, due to constraints such as the lack of teacher skills in using technology, inadequate facilities, and financial constraints.